Comparison of Face-to-Face and Electronic Education Methods on Anxiety in Patients with Acute Myocardial Infarction - Amin Saki; Abbas Hooshmand Bahabadi; Ahmad Ali Asadi Noghabi; Abbas Mehran (Tehran University of Medical Sciences, 2014)
Background & Aim: Lack of knowledge about acute myocardial infarction and its treatment result in feeling anxious among the patients. Implementing appropriate educational methods can decrease anxiety in patients with acute myocardial infarction. This study was conducted to compare effects of two educational methods (face-to-face and electronic educational methods) on anxiety among patients with acute myocardial infarction .   Methods & Materials: This was an experimental study in which 105 patients hospitalized with acute myocardial infarction in the "CCUs" of three educational hospitals were selected based on eligibility criteria and were allocated into three groups including face-to-face educational group, electronic education group, and control group using block randomized allocation. Data were collected using demographic check-list and the Spielberger state-trait anxiety inventory questionnaire. The level of anxiety was measured before and immediately after the interventions in all three groups. Data were analyzed in the SPSS-16.   Results: Both educational methods reduced anxiety significantly in patients with acute myocardial infarction. There were no significant difference between the two educational method groups in the anxiety level (P=0.94) .   Conclusion: Both face-to-face and electronic educational methods reduced anxiety in patients with acute myocardial infarction. It is recommended that nurses use one of these educational methods to reduce anxiety among the patients .